TANTANGAN MEMBELAJARKAN MATA PELAJARAN ILMU PENGETAHUAN SOSIAL DI SEKOLAH DASAR: STUDI LITERATUR - Ahmad Syukur; Muhammad Fashihullisan; Erik Aditia Ismaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Social Studies (IPS) is a strategic subject in shaping the character and social awareness of students since elementary school level. However, in practice, IPS learning in Elementary Schools (SD) faces various complex and multidimensional challenges. This study aims to analyze these challenges through a literature study approach to nine nationally indexed scientific articles. The results of the study show that the challenges of IPS learning include the low image of the IPS subject, limited teacher competence in implementing the Independent Curriculum, minimal integration of global issues and 21st century literacy, and lack of infrastructure and technology support. Therefore, a systemic approach is needed through teacher training, provision of resources, curriculum strengthening, and pedagogical transformation to make IPS a meaningful, adaptive, and contextual learning medium.